PENGGUNAAN MEDIA GAMBAR DALAM MEMOTIVASI MINAT BELAJAR ANAK USIA DINI KELAS B4 TK NEGERI PEMBINA KECAMATAN SABANGAU - Handriani J.H; Rudie; Dwi Sartica (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of picture media in motivating early childhood learning interest, as well as to identify its supporting and inhibiting factors in class B4 at TK Negeri Pembina, Sabangau District. A qualitative descriptive approach was employed. Primary data were collected through observation and interviews with the principal, classroom teacher, and parents. Secondary data were supported by document studies, including lesson plans, student reports, school profiles, and learning activity photographs. Data analysis techniques were conducted through data collection, data reduction, data display, and drawing conclusions. The results showed that the use of picture media was implemented through three main stages: planning (selecting bright, simple, and relevant pictures while involving children's choices), presentation (displaying one main visual object followed by contextual question-and-answer sessions), and evaluation (assessing fine motor skills through worksheets and expressive language skills in retelling the pictures). This method successfully increased learning interest, characterized by focused attention, high enthusiasm, active participation in class, and the emergence of independent motivation at home. The supporting factors included adequate school visual facilities, teachers' professional competence, and a classroom environment rich in visual stimuli. The inhibiting factor was the children's naturally short attention span, which was successfully overcome by the teacher's intervention through ice-breaking activities, light physical movements, and educational singing.